Home over institution? New insights on older adults’ care preferences from a mixed-methods study in France - Anaïs Cheneau; Jonathan Sicsic; Thomas Rapp (PLoS ONE, 2026)
As populations age, long-term care policies must balance individual preferences with financial constraints. The prevailing “aging in place” policy in France assumes that citizens overwhelmingly prefer home care over nursing homes. However, little is known about people’s preferences towards long-term care options before disability occurs. We elicit preferences among community-dwelling adults over 60 using a mixed-method approach: qualitative interviews and a two-stage D-efficient discrete choice experiment. In each task, respondents chose between two hypothetical nursing homes varying in professional care quality, living environment, out-of-pocket (OOP) cost, and proximity, then decided whether to receive care in this nursing home or remain at home. A sample of 2,886 French adults over 60 completed the survey in 2024. We used random-effect conditional logit and latent class logit models to investigate trade-offs and preference heterogeneity. While a majority (54%) consistently favored home-care, 37% shifted their decision in response to improved nursing home characteristics. Professional care quality and living environment influenced choices as strongly as OOP cost, while proximity plays a secondary role. Strengthening staffing and training, upgrading equipment and the conviviality of shared spaces, and containing OOP costs are direct levers to raise the acceptability of nursing home care.